Kedo file system for root canal preparation in primary teeth - Ganesh Jeevanandan; Sagareeka Ganesh; Arthilakshmi (Wolters Kluwer Medknow Publications, 2019)
Endodontic instruments play a vital role during root canal preparation. Biomechanical preparation in primary teeth is performed using the adult endodontic files. There are various disadvantages during use of adult endodontic files in primary teeth namely the length and taper of the files. Recently, an exclusive paediatric endodontic file system has been introduced for cleaning and shaping of primary root canals. This short communication describes the use of exclusive Kedo-SH manual and Kedo-S rotary file system in primary teeth.